Color atlas of chemical peels - Grimes, Pearl E.; De Padova, Maria Pia; Tosti, Antonella (Springer Berlin Heidelberg, 2012)
Chemical peeling is a well-known method used to restore a more youthful appearance and improve dermatologic defects.  In recent years the technique has been marked by constant innovation. This book is the first atlas on chemical peels and has been significantly revised and updated since the first edition so as to reflect the state of the art in the field.  The various types of chemical peel and peeling techniques, including new combined procedures, are first discussed in a step-by-step manner with the aid of supporting illustrations.  Pathogenesis and treatment options are then considered, with each author reporting on his or her personal experience and preferred approach for different diseases and conditions, including acne, rosacea, melasma, photoaging, postinflammatory hyperpigmentation, actinic keratosis, and dark skin. An entirely new section addresses how to deal with side-effects and complications of the different procedures.  This atlas has been specifically designed as a reference tool for dermatologists who deal with cosmetology.  In particular, by providing clear and practical information on the different peeling procedures and their indications, it will prove invaluable for dermatologists and other doctors who wish to start performing chemical peels.